The Geographic Determinants of Economic Growth and the Increasing Albania-Kosovo Trade Relations - Mehmeti, Valbona (Journal of Economic Development, Environment and People, 2020)
For the last few years, the trade volume between Albania and Kosovo has increased considerably, clearly showing that, on top of many other factors, the geographic determinants of economic growth and development must never be underestimated. On the other hand, the ever-closer economic integration of Albania and Kosovo is only natural and should not be considered as a cause for political rifts in the Western Balkans. The paper will go through the various documents and agreements adopted by Tirana and Pristina to promote mutual trade relations, and it will refer to an abundance of data indicating the improving trade relations. Subsequently, the paper will shed light on the patterns of economic behavior that Albania and Kosovo show, a behavior which can be better comprehended under the framework of geographic determinants of economic growth and development, such as location, resources, food productivity, population and population growth, regionalization, culture, etc.